THE EFFECT OF BOMB METHOD (BREASTCARE, OXYTOCIN MASSAGE, AND MARMET TECHNIQUE) ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Silvia, Silvia Putri; Yanti, Ariu Dewi; Heni, Heni Frilasari (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
The smooth process of lactation or the production and release of breast milk is influenced by breast care, frequency of breastfeeding, mother's psychology, mother's health, and contraception. The decrease in milk production is also caused by a lack of the hormones prolactin and oxytocin which play a role in the lactation process. This study aims to determine the effect of BOM method on milk production in post partum mothers. Quasy experimental research design with a Static Group Comparison approach. The population in this study were all post partum mothers in the Working Area of the Melonguane Public Health Center, Talaud Islands Regency in December 2022-January 2023 as many as 34 people. Data collection used purposive sampling, so that a sample of 32 people was obtained. The research instrument used the SOP for the BOM method and a checklist for breast milk production. Data analysis using the Mann Whitney Test. The results showed that all milk production in the intervention group was good, as many as 16 respondents (100%), while in the control group, most were good, as many as 9 respondents (56.3%). The results of the Mann Whitney test showed that the p value (0.000) < ???? (0.05) so that Ho was rejected and H1 was accepted, meaning The BOM method has been proven to increase milk production in Post Partum Mothers so as to increase the degree of optimal growth and development for baby